2000
DOI: 10.1111/j.1651-2227.2000.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of children with cow's milk allergy in infancy by 10 years of age

Abstract: To assess the development of milk protein tolerance and atopic diseases in children diagnosed for cow's milk allergy (CMA) in infancy, we conducted re‐examinations of 56 CMA subjects at the age of 10 y using 204 age‐matched controls. The children underwent clinical examinations and skin prick tests (SPT), and their IgE‐specific antibodies to milk and five other food allergens were determined. By the age of 10 y, all but four subjects had become tolerant to at least small amounts of milk protein. However, gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
0
12
0
3
Order By: Relevance
“…Curiously, Tikkanen et al. (20) compared 56 10‐yr‐old children with CMA with age‐matched healthy controls and showed that CMA in infancy increases the risk of developing other atopic diseases and allergic sensitization with a natural course that is independent of the eventual persistence of CMA.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, Tikkanen et al. (20) compared 56 10‐yr‐old children with CMA with age‐matched healthy controls and showed that CMA in infancy increases the risk of developing other atopic diseases and allergic sensitization with a natural course that is independent of the eventual persistence of CMA.…”
Section: Discussionmentioning
confidence: 99%
“…In this context it is interesting to note that, in some children affected by cow milk allergy during infancy, a local ratio of gastrointestinal diseases, such as recurrent abdominal pain, may persist 22,23.…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro estudio, la presencia de antecedentes familiares de atopia fue inferior a la reflejada en otros 8,11 . El porcentaje de pacientes que presentaba más de una manifestación atópica fue similar a otros estudios 12 . El porcentaje que alcanzó tolerancia fue similar al encontrado por Dias 13 en Portugal a los diez años, aunque en sus estudios no todos presentan alergia IgEmediada, lo mismo ocurría con la muestra del estudio de Tikkanen 12 .…”
Section: Resultsunclassified
“…El porcentaje de pacientes que presentaba más de una manifestación atópica fue similar a otros estudios 12 . El porcentaje que alcanzó tolerancia fue similar al encontrado por Dias 13 en Portugal a los diez años, aunque en sus estudios no todos presentan alergia IgEmediada, lo mismo ocurría con la muestra del estudio de Tikkanen 12 . En nuestro estudio existe una tendencia a que los niños con manifestaciones respiratorias de atopia (asma y/o rinoconjuntivitis) alcancen la tolerancia más tarde.…”
Section: Resultsunclassified